Earthquake History and Rupture Extents from Morphology of Fault Scarps Along the Valley Fault System (Philippines) - Rolly E. Rimando; Peter L. K. Knuepfer (GeoHazards, 2025)
The morphologic dating of single-event fault scarps along the dextral strike-slip Valley Fault System (VFS) yielded distinct clusters of relative ages (kt), which we interpret as evidence of independent surface ruptures. The boundaries between structural and geometric segments of the East Valley Fault (EVF) appear to have been nonpersistent during the recent rupture cycle. We associate the youngest cluster with the largest historical earthquake (M > 7 in 1863) felt in Manila, which is believed to have come from three segments of the EVF. Thus, future multiple-segment events, M > 7, could occur on the EVF. Our results do not support rupturing of the entire length of the West Valley Fault (WVF), but its northern segment (segment I) is capable of generating an M > 7 earthquake. This is the first time that diffusivity and relative ages of fault scarps are determined from this part of the world and is one of the few studies applying analysis of recent fault scarps to rupture segmentation studies. The recent scarps along the WVF’s segment II are due to aseismic creep and occur along pre-existing tectonic structures. Continued groundwater overextraction within the creeping zone could induce seismicity and modulate the natural timing of future earthquakes along the WVF.